Edukasi tentang Menstruasi pada Remaja Putri di SMP Negeri 1 Mamuju - Thalib, Kiki Uniatri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Menstrual Hygiene Managemen is a strategy for managing hygiene and health during the menstrual period to keep it clean and healthy. When women menstruate, they need to use sanitary napkins to collect the blood that comes out of the vagina and this is related to menstrual hygiene. Menstruation is increasingly recognized as an issue in domestic and global public health. In addition, matters related to menstruation are still considered taboo and have a negative stigma and it is often difficult to practice optimal menstrual hygiene for adolescents and adults in various countries and regions. Many girls do not have a proper understanding that menstruation is a normal biological process. They actually only know about it during menarche, aka when they first experience menstruation. This community service activity was carried out in the Hall of SMP Negeri 1 Mamuju with a total of 49 young women using the counseling method in the form of lectures. From this Community Service Activity, it was concluded that the implementation of menstruation education for young women in the Mamuju 1 Middle School Hall went well, as many as 49 people took part in this activity with enthusiasm as seen from the responses of children who paid close attention and also asked questions during the Q&A session.